The role of political connections in moderating the impact of CEO characteristics on financial perfomance: An emprical study of energy companies in Indonesia - Arafat. A, Lathif (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study aims to explore the role of CEO political connections in moderating the relationship between CEO characteristics and financial performance in Indonesia's energy sector. Using a sample of 73 energy companies listed on the Indonesia Stock Exchange from 2020 to 2024, the study collects secondary data on CEO tenure, age, education, and political connections. Multiple regression analysis with the Fixed Effect model was used to test the hypotheses. The results show that CEO education has a significant positive impact on financial performance, measured by Return on Assets (ROA). CEO political connections were found to strengthen the relationship between CEO education and company financial performance. In contrast, CEO tenure and age did not have a significant effect on financial performance. These findings suggest that in Indonesia's dynamic and heavily regulated energy sector, CEO education is a crucial factor in improving financial performance, especially when supported by political connections that provide access to strategic resources. Political connections also weaken the impact of CEO age on performance but enhance the positive effect of CEO education. This study contributes to the literature by highlighting the interaction between CEO characteristics and political connections in the highly regulated energy sector in Indonesia, emphasizing the importance of adaptive leadership strategies in navigating regulatory challenges.